Understanding near infrared spectroscopy and its application to skeletal muscle research - Barstow, T. J. (Journal of Applied Physiology, 2019)
Near infrared spectroscopy (NIRS) is a powerful noninvasive tool with which to study the matching of oxygen delivery to oxygen utilization and the number of new publications utilizing this technique has increased exponentially in the last 20 yr. By measuring the state of oxygenation of the primary heme compounds in skeletal muscle (hemoglobin and myoglobin), greater understanding of the underlying control mechanisms that couple perfusive and diffusive oxygen delivery to oxidative metabolism can be gained from the laboratory to the athletic field to the intensive care unit or emergency room. However, the field of NIRS has been complicated by the diversity of instrumentation, the inherent limitations of some of these technologies, the associated diversity of terminology, and a general lack of standardization of protocols. This Cores of Reproducibility in Physiology (CORP) will describe in basic but important detail the most common methodologies of NIRS, their strengths and limitations, and discuss some of the potential confounding factors that can affect the quality and reproducibility of NIRS data. Recommendations are provided to reduce the variability and errors in data collection, analysis, and interpretation. The goal of this CORP is to provide readers with a greater understanding of the methodology, limitations, and best practices so as to improve the reproducibility of NIRS research in skeletal muscle.